Dharmaśāstra vis-à-vis Mokṣaśāstra: The Special Position of the Veda in the Philosophies in India - Ramkrishna Bhattacharya (Universidad de San Buenaventura, 2018)
The principal philosophical systems of India are divided into two branches: āstika and nāstika. This division, however, is basically religious, not philosophical or logical. Whatever might have been the original meanings of these two terms, so far as Indian philosophical literature is concerned, āstika means Veda-abiding and nāstika, non-Veda-abiding. This is an instance of the intrusion of Dharmaśāstra into Mokṣaśāstra: the rules of religious law operating on what was claimed to be the science of freedom (mokṣa/mukti). Thus, religious law had its position asserted and the materialists along with the Jains and the Buddhists were declared to be outside the Vedic fold.